Penerapan Konseling Cognitive Behaviour Therapy Menggunakan Personal Achievment Sheet Untuk Meningkatkan Self Confidence Pada Siswa SMP Plus Abdul Aziz - Mukarromah, Siti; Rahmawati, Weni Kurnia; Fauziyah, Nailul (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
his research aims to evaluate the effectiveness of implementing Cognitive Behavioral Therapy (CBT) counseling using the Personal Achievement Sheet (PAS) media as an effort to increase the level of self-confidence of Plus Abdul Aziz Jember Middle School students. Self-confidence plays an important role in students' personal development and academic achievement, so effective intervention strategies are crucial in the educational context. This research method uses an experimental approach with a pre-test and post-test design and a control group. The sample consisted of 14 students divided into 2 groups, namely the control group and the experimental group. The results of the analysis of the paired sample T-test showed a sig (2-tailed) score of 0.001 < 0.05, which means there was an increase in self-confidence because there was a significant difference in students' self-confidence before and after being given treatment. The data will provide an in-depth understanding of the extent to which the application of CBT counseling using PAS media can make a significant contribution to increasing students' self-confidence compared to conventional counseling methods.